New Acyloxymethyl Ketones: Useful Probes for Cysteine Protease Profiling - Coman, Anca G.; Paraschivescu, Codruta C.; Hadade, Niculina D.; Juncu, Andrei; Vlaicu, Ovidiu; Popescu, Costin-Ioan; Matache, Mihaela (Synthesis, 2016)
Peptidyl-acyloxymethyl ketones (AOMKs) belong to a class of selective, irreversible inhibitors (activity-based probes) widely used as chemical tools of investigating proteins, for example, in activity-based protein profiling. The synthesis of the AOMKs has always been challenging and current methodologies involve both solution and solid-phase synthesis. Herein, the synthesis of a new scaffold useful for the preparation of peptidyl-AOMKs is reported and it is demonstrated that the new synthetic probes bearing a 4-functionalized 2,6-dimethylbenzoate efficiently inhibit cysteine proteases like cathepsin B.
Keywords: acyloxymethyl ketones; activity-based probes; peptidyl-AOMKs; 2,6-dimethylbenzoates; solid-phase peptide synthesis